2016
DOI: 10.1088/1367-2630/18/1/013051
|View full text |Cite
|
Sign up to set email alerts
|

Particle-in-cell simulations of electron energization in laser-driven magnetic reconnection

Abstract: Electrons can be energized during laser-driven magnetic reconnection, and the energized electrons form three super-Alfvénic electron jets in the outflow region (Lu et al 2014 New J. Phys. 16 083021). In this paper, by performing two-dimensional particle-in-cell simulations, we find that the electrons can also be significantly energized before magnetic reconnection occurs. When two plasma bubbles with toroidal magnetic fields expand and squeeze each other, the electrons in the magnetic ribbons are energized thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
(65 reference statements)
2
13
0
Order By: Relevance
“…For example, three well-collimated high-speed electron jets were observed in the fanlike outflow region in experiments [6,14], which are consistent with the signatures of MR simulations [15]. Fully kinetic particle simulations showed that fast reconnection in these strongly driven systems can be explained by magnetic flux pileup at the shoulder of the current sheet [16]. However, most of the simulations did not include the laser-plasma interaction stages, by simply assuming that two bubbles with high energy electron currents start to evolve in a background plasma.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, three well-collimated high-speed electron jets were observed in the fanlike outflow region in experiments [6,14], which are consistent with the signatures of MR simulations [15]. Fully kinetic particle simulations showed that fast reconnection in these strongly driven systems can be explained by magnetic flux pileup at the shoulder of the current sheet [16]. However, most of the simulations did not include the laser-plasma interaction stages, by simply assuming that two bubbles with high energy electron currents start to evolve in a background plasma.…”
Section: Introductionsupporting
confidence: 60%
“…With the development of ultrashort high power laser technologies, petawatt lasers with picosecond to femtosecond durations are available nowadays. This makes it possible to investigate fast magnetic field generation and dissipation under even higher quasi-static magnetic fields over 100 MG by the relativistic intense lasers interaction with plasmas [2,[16][17][18] or by the interaction of high current relativistic electron beams with plasmas [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulations have considered the reconnection in parameter regimes of HEDP plasmas, and with model geometries of colliding bubbles to assess reconnection mechanisms and particle acceleration. Simulations have demonstrated the role of flux pile-up [36], the breakup of the current sheet into multiple islands at large system size [37], and have documented mechanisms for generating electron jets and accelerating particles [38,43,51,52]. Recent kinetic simulations have also studied Biermannbattery magnetic field generation in collisionless plasmas with model initial conditions [53].…”
Section: Magnetic Field Generation and Evolution In Laser-drivenmentioning
confidence: 99%
“…The reason is that the shorter rising time will result in a faster expansion of the magnetic bubbles. During the expansion, particles are reflected and accelerated by the magnetic bubbles; they can also get Fermi acceleration when trapped between the two approaching bubbles, 40 and the acceleration will be more significant when the expanding speed becomes larger. 27 This process will lead to a stronger dissipation of the magnetic energy and smoothens the magnetic gradient in the reconnection upstream.…”
Section: -4mentioning
confidence: 99%